Assessment of sectoral innovation systems approach: The case of Turkish internet service market - Ayhan Tözer; Yavuz Göktaylar (International Telecommunications Society (ITS), 2011)
The aim of this paper is to evaluate sectoral innovation system of Turkish internet service market by looking into some case studies and making interviews with related actors. In this attempt, firstly, a sectoral innovation systems approach has been described briefly from theoretical point of view. Then, third section introduces sectoral innovation systems of internet services. At fourth section, two case studies are mentioned. At the following chapter, we focus on regulatory developments that affect market and sectoral innovation systems regarding broadband internet access in Turkey. Fourthly, we describe the results of interviews done with executive officers of several large Internet Service Providers and a general secretary of a sector association in this country. Finally, we discuss the policy implications for Turkish policy makers in order to improve the functioning of sectoral innovation systems of internet services. At the conclusion section, we summarize the main findings and policy suggestions.
Keywords: L51; L96; 330; competition; innovation; internet service market; sectoral innovation system; telecommunications; regulation.